The empirics of UK gilts' yields - Tanweer Akram; Huiqing Li (Levy Economics Institute of Bard College, 2020)
This paper analyzes the nominal yields of UK gilt-edged securities ("gilts") based on a Keynesian perspective, which holds that the short-term interest rate is the primary driver of the long-term interest rate. Quarterly data are used to model gilts' nominal yields. These models bring to light the complex dynamics relating the nominal yields on gilts to the short-term interest rate, inflation, the growth of industrial production, and the government debt ratio. The results show that the short-term interest rate has a crucial influence on the nominal yields on gilts, even after controlling for various factors. Contrary to widely held views, a higher government debt ratio does not lead to higher nominal yields.
Keywords: E43; E50; E58; E60; G10; G12; 330; UK Gilt-Edged Securities; Government Bonds; Long-Term Interest Rates; Nominal Bond Yields; Government Debt